2020
DOI: 10.1016/j.intimp.2020.106995
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between premorbid IL-6 levels and COVID-19 mortality: Potential role for Vitamin D

Abstract: Highlights Interleukin IL-6 facilitates COVID-19 viral cell entry and replication. Healthy IL-6 levels correlate with COVID-19 morbidity in similar matched populations. Vitamin D administration appears to lower IL-6 levels in humans. IL-6 modulation with Vitamin D and other means may be a useful therapeutic strategy in COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 45 publications
(63 reference statements)
2
24
0
3
Order By: Relevance
“…Acute respiratory distress syndrome in COVID-19 infection is thought to be secondary to dysregulation of the immune system. Several authors have highlighted abnormally high levels of proinflammatory cytokines in patients developing severe forms of COVID-19 infection with pulmonary involvement and acute respiratory distress [9,10,37]. Some authors have suggested that vitamin D could be active on the immune and respiratory systems [38], notably by modulating cytokine production [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acute respiratory distress syndrome in COVID-19 infection is thought to be secondary to dysregulation of the immune system. Several authors have highlighted abnormally high levels of proinflammatory cytokines in patients developing severe forms of COVID-19 infection with pulmonary involvement and acute respiratory distress [9,10,37]. Some authors have suggested that vitamin D could be active on the immune and respiratory systems [38], notably by modulating cytokine production [13].…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory distress most often occurs more than seven days after the onset of symptoms [5] and is frequently observed in aged people [6][7][8]. Several authors have demonstrated abnormally high levels of proinflammatory cytokines in patients developing severe forms of COVID-19 infection [9,10]. In light of this, it has been suggested that the respiratory complications of COVID-19 infection occurring beyond day seven were due to a dysregulation of the immune system, termed the "cytokine storm" [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrast this with Vitamin D, which lowers immune cell IL-6 production ( Silberstein, 2020a ), potentially reducing pro-inflammatory effects, but does not specifically target IL-6 receptors, avoiding any deleterious effect on the anti-inflammatory actions of IL-6. Vitamin D has also been shown to lower TNF levels ( Peterson and Heffernan, 2008 ), representing an additional therapeutic mechanism for countering the COVID-19 cytokine storm.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D, which has immunomodulatory properties (Sassi et al, 2020), was proposed as a potential therapeutic option in the early part of the pandemic ( Silberstein, 2020b ), supported in part by reports of Vitamin D deficiency resulting in poorer outcomes (see the review by Benskin, 2020 ). Yet, despite calls for clinical trials of this vitamin ( Silberstein, 2020b ), in part based upon its modulation of IL-6, a key interleukin implicated in viral replication ( Silberstein, 2020a ), only a few have been completed at time of writing. This comes as a surprise, given the widespread promotion and multiple trials of the IL-6 antagonist tocilizumab ( Tleyjeh et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%